Content Validity of Needs Analysis Questionnaire Instrumentation for the Development of EduComic Model/ Kesahan Kandungan Instrumen Soal Selidik Analisis Keperluan untuk Pembangunan Model EduComic (Sains Humanika, 2025)
This study aims to evaluate the content validity of the needs analysis questionnaire instrument for the development of the EduComic Model, using the Content Validity Index (CVI) assessed based on the views of five experts. The assessment of content validity was conducted through the application of the Item-Level Content Validity Index (I-CVI) and the Scale-Level Content Validity Index (S-CVI). The study findings show that the overall S-CVI (average) score for the dimensions of teachers’ perceptions, teachers’ constraints in teaching and learning science, the need for EduComic Model development, and learning within the EduComic Model was 1.00. The S-CVI (UA) for each dimension in the needs analysis for the EduComic Model development was also at a score of 1.00, meeting the required criteria for the overall S-CVI value of the needs analysis questionnaire instrument for the EduComic Model development. In conclusion, the 60 items in the needs analysis questionnaire were accepted and retained to assess the needs analysis for the development of the EduComic Model in the pilot study for the purposes of construct validity and instrument reliability.
Keywords: Content Validity, EduComic Model, Needs Analysis, Questionnaire, Reliability, And Primary School.